2014
DOI: 10.1037/a0037075
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processing therapy for veterans with posttraumatic stress disorder: A comparison between outpatient and residential treatment.

Abstract: This is the 1st study to compare pretreatment characteristics and treatment outcome between veterans receiving outpatient and residential PTSD treatment. Findings may help clinicians select appropriate care for their patients by identifying relevant pretreatment characteristics and generally informing expectations of treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 35 publications
(44 reference statements)
6
59
0
Order By: Relevance
“…This adds to the findings of Walter et al. (), who found that veterans in residential treatment had more severe PTSD and depression versus those in outpatient treatment. The current study findings suggest that higher disability severity in mobility may also explain why certain veterans enter residential versus outpatient PTSD treatment.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This adds to the findings of Walter et al. (), who found that veterans in residential treatment had more severe PTSD and depression versus those in outpatient treatment. The current study findings suggest that higher disability severity in mobility may also explain why certain veterans enter residential versus outpatient PTSD treatment.…”
Section: Discussionsupporting
confidence: 65%
“…The only difference between residential patients versus outpatients on the WHODAS 2.0 scales was that residential patients had higher WHODAS 2.0 Mobility scores. This adds to the findings of Walter et al (2014), who found that veterans in residential treatment had more severe PTSD and depression versus those in outpatient treatment. The current study findings suggest that higher disability severity in mobility may also explain why certain veterans enter residential versus outpatient PTSD treatment.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Third, veterans were not asked to record the duration of their mindfulness practice, which makes it difficult to determine the level of practice veterans achieved, beyond their participation in seven sessions during which mindfulness skills were taught. Fourth, the findings from the present study may not be generalizable to veterans who are seeking care outside of residential treatment programs for PTSD, as significant differences between veterans in residential and outpatient treatment programs have previously been noted (e.g., Walter, Varkovitzky, Owens, Lewis, & Chard, 2014).…”
Section: Discussionmentioning
confidence: 73%